Odraz interkulturních vztahů v srbské a rumunské frazeologii Reflection of Intercultural Relations in Serbian and Romanian Phraseology - Barbora Krucká (Studia Mythologica Slavica, 2014)
This research examines the reflection of intercultural relations of Serbian and Romanian speech community members in their phraseology. It also focuses at the auto-stereotypes and hetero-stereotypes present in phraseology. As a shared collective experience imposed in the language, phraseology also entails the summary of judgments about the world of a particular speech community, and thus its relationship to its own culture, as well as to different cultures. Proverbs and phrases from the collections of proverbs form a corpus, which is quantitatively analysed. This results in a view of perception of their own nation and ethnical, national and religious groups members in prolonged contact with Serbian and Romanian speech community.